Full 3D layout reconstruction from one single 360º image - Fernández Labrador, Clara; Pérez Yus, Alejandro; López Nicolás, Gonzalo; Guerrero Campo, José Jesús (Jornada de Jóvenes Investigadores del I3A, 2018)
We propose an entire pipeline which receives as input a 360º panorama and returns a closed, 3D reconstruction of the room faithful to its actual shape. We exploit deep learning combined with geometry to obtain structural lines, and thus structural corners, from which we generate final layout models assuming Manhattan world.